2016
DOI: 10.5301/uro.5000212
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term follow-up of Trigonoplasty Antireflux Operation

Abstract: Trigonoplasty success rate can decrease with long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…We had no complications such as mentioned one or ureteral obstruction; however, just in one case, we observed bladder dehiscence. Applying this modified technique resulted in high success rate, compatible with Gil-Vernet report [ 16 ]; however, Sharifiaghdas et al have recently reported the lower success rate with long-term follow-up by trigonoplasty [ 17 ]. This technique is simple, safe, and least invasive.…”
Section: Discussionsupporting
confidence: 74%
“…We had no complications such as mentioned one or ureteral obstruction; however, just in one case, we observed bladder dehiscence. Applying this modified technique resulted in high success rate, compatible with Gil-Vernet report [ 16 ]; however, Sharifiaghdas et al have recently reported the lower success rate with long-term follow-up by trigonoplasty [ 17 ]. This technique is simple, safe, and least invasive.…”
Section: Discussionsupporting
confidence: 74%